2008
DOI: 10.1097/ede.0b013e3181812beb
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Disinfection By-Product Exposure and Duration of Gestation

Abstract: The probability of preterm birth was not increased with high DBP exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…The OR for with term LBW was 1.00 (95% CI 0.91 to 1.10), for SGA it was 0.96 (95% CI 0.91 to 1.02) and for PD 1.08 (95% CI 0.98 to 1.18). Similar to findings of our study, there is limited evidence to date that indicates an association between PD and THMs5 8 32–35 while Hoffman et al 13 reported that average residential second trimester THMs levels were associated with lower risk of PD. Several studies have reported a small increased risk of delivering an SGA infant among women exposed to high levels of THMs (>80 μg/l)8 11 36 37 while a recent cohort study did not observe an association 10.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The OR for with term LBW was 1.00 (95% CI 0.91 to 1.10), for SGA it was 0.96 (95% CI 0.91 to 1.02) and for PD 1.08 (95% CI 0.98 to 1.18). Similar to findings of our study, there is limited evidence to date that indicates an association between PD and THMs5 8 32–35 while Hoffman et al 13 reported that average residential second trimester THMs levels were associated with lower risk of PD. Several studies have reported a small increased risk of delivering an SGA infant among women exposed to high levels of THMs (>80 μg/l)8 11 36 37 while a recent cohort study did not observe an association 10.…”
Section: Discussionsupporting
confidence: 89%
“…Total uptake exposure through ingestion, shower and bathing was not estimated in most previous studies with only a few studies found to have performed a similar analysis 10 13 20 21. Our results highlighted the importance of dermal and inhalation exposure, as women reported that they took showers and baths frequently, similar to populations in other studies 12 30.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, an excess of SGA could result from a reduction in fetal growth or from an excess of preterm births. Our companion paper 41 shows that, rather than an excess of preterm births in these data, we observed a lower risk for preterm delivery among highly exposed women. Restricting our SGA analyses to infants born at Ն37 weeks completed gestation also did not change our findings.…”
Section: Discussionsupporting
confidence: 49%
“…Other studies found no association between HAA exposure and fetal growth or PTD. 9,[15][16][17] The lack of adequate exposure gradients is an even larger issue for HAAs, especially when examining individual HAA constituents, given their lower overall concentrations in most drinking water supplies.…”
mentioning
confidence: 99%